2003
DOI: 10.1046/j.1464-410x.2003.04355.x
|View full text |Cite
|
Sign up to set email alerts
|

Partner's influence on patient preference for treatment in early prostate cancer

Abstract: RESULTSQuestionnaires were sent to 116 eligible patients and 82 were returned for analysis (mean partner age 63 years). When asked to recall the treatment options initially discussed, all partners recalled radiotherapy (EBRT), all but one radical prostatectomy (RP), 51% brachytherapy, but only 29% watchful waiting (WW); 41% of partners stated RP as their chosen option, 37% EBRT, 12% brachytherapy and 10% no clear favourite. None preferred WW. Employment and education status were not significant predictors of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 19 publications
1
62
1
4
Order By: Relevance
“…These included 16 survey studies, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] 16 studies aimed at designing and exploring decision aids, 19 -34 16 focus group studies regarding treatment decision making, [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] 10 studies examining shared decision making between patients and physicians, [51][52][53][54][55][56][57][58][59][60] 6 studies exploring health state preferences associated with treatment decision making, [61][62][63][64][65][66] and 5 review articles related to treatment decision making.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These included 16 survey studies, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] 16 studies aimed at designing and exploring decision aids, 19 -34 16 focus group studies regarding treatment decision making, [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] 10 studies examining shared decision making between patients and physicians, [51][52][53][54][55][56][57][58][59][60] 6 studies exploring health state preferences associated with treatment decision making, [61][62][63][64][65][66] and 5 review articles related to treatment decision making.…”
Section: Resultsmentioning
confidence: 99%
“…In 1 study, 70% of men who received a recommendation for surgery selected another therapy. 10 Other studies have found that approximately two-thirds 45 and three-quarters 7 of patients, respectively, see at least 2 physicians.…”
Section: Framing and Interpreting Influences In Prostate Cancer Decismentioning
confidence: 99%
See 3 more Smart Citations